Rotas turísticas para o município de Itaara - RS: uma leitura geográfica da paisagem e do lugar - Dietrich, Sinara Sarassua (2011)
This dissertation is the result of research conducted by the Graduate Program in Geography and Geosciences, Federal University of Santa Maria, and aims to characterize the phenomena that have potential for tourism in the municipality as well as the socioeconomic conditions that can be consolidated through deployment of tourist routes which value the place. The village that gave rise to the municipality of Itaara began with the construction of the old Sting Pinhal (current road Perau), which was the main link between the central plateau and the peripheral depression. Later, with the implementation of the railway, there was the creation and expansion of trade in central state. The municipality of Itaara draws attention for its natural beauty, its scenic landscape, biodiversity of flora and fauna, the warm and modeled relief, located in the ridge of the Serra Geral, as well as valuable historical heritage, which must be preserved, valued and recognized as a tourism product. For assessment of the tourism phenomenon in place the elements were analyzed infrastructure, environment, local population and public policies for tourism, as well as their interrelationships. In developing the research sought to achieve the goals of searching through various methodologies appropriate to each segment of the research appealed to Milton Santos in seeking to understand the relationship of tourism and place in globalization, systemic methodology taking place like space / concept, based on Bertalanffy, Morin and Beni in the treatment of certain component elements of the system in question. It is also used a humanistic approach, considering important factor in the perception of the local population in relation to tourism activities in the city, supported by Y-Fu Tuan. The results were obtained through literature search and direct, with interviews held in (field work), and photographic records of certain segments of the landscape and existing socioeconomic activities, as well as changes in infrastructure that are being held. The tourism potential was analyzed and organized into four tourist routes: Route of Ecotourism Itaara, Route Perau Road, Route and historical-cultural Route resorts, in order to assist in the organization as a county inmate Itaara of tours in the scenario gaucho